PRODUCTIVE WAQF DEVELOPMENT THROUGH ASSET-BASED COMMUNITY DEVELOPMENT IN LWP NU BENGKULU - Wani, Ranti Sri; Anggara, Kurnia; Arisandy, Yosy; Yustati, Herlina; Een F, Yunida; Mayang, Sekar (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
Waqf holds significant potential as a means of promoting socio-economic empowerment within Muslim communities. However, its management is often hampered by the limited availability of professional human resources. The Nahdlatul Ulama Waqf and Land Institution (LWP NU) Bengkulu, as a newly established organization, faces similar challenges, including a lack of mentoring, insufficient structural support, and limited institutional facilities. To address these issues, this community engagement program was initiated to strengthen the capacity of waqf human resources using the Asset-Based Community Development (ABCD) approach. The program was carried out through four stages: discovery (identifying assets), dream (formulating a shared vision), design (planning programs), and destiny (ensuring sustainability). Key assets leveraged in this process included the active involvement of students from the Zakat and Waqf Management and Islamic Economics study programs at Fatmawati Sukarno University Bengkulu. The findings show that applying the ABCD approach enabled the institution to map its available assets and develop productive waqf initiatives such as kios waqf, book waqf, Iqro waqf, and Qur’an waqf. The program also led to tangible benefits, including improved student skills in waqf management, greater institutional participation, and stronger collaboration between universities and community organizations. Overall, the ABCD approach has proven effective in empowering waqf human resources while opening pathways for the sustainable growth of productive waqf at the local level. Keywords : community service, ABCD, productive waqf, human resources, LWP NU.